MASCULINITY TRAITS OF MAUD WATTS AS A FEMALE CHARACTER IN THE SUFFRAGETTE FILM - Rastina, Rastina; Sili, Surya; Nasrullah, Nasrullah (Fakultas Ilmu Budaya Universitas Mulawarman, 2019)
This study is aimed to reveal how a female character is depicted in the film and to prove that a female character also adopted masculinity traits. The theory of characterization by Boggs and Petrie is used to reveal the depiction of Maud’s character, while to prove that Maud Watts adopted masculinity traits, the writer used the theory of Bem Sex Role Inventory by Sandra L. Bem. This study is conducted as a qualitative content analysis, which adopts the technique of coding categories. The findings of this study reveal that as a female character, Maud Watts is not only adopted femininity traits but also masculinity traits. Maud’s character is depicted through the five tools of characterization according to Boggs and Petrie. Through her appearances, she is masculine and likeable. Through the dialogues, she is independent, confident, ambitious, assertive, competitive, sympathetic and loyal. Through her external action, Maud is ambitious, sympathetic, aggressive and loyal. Through her internal actions, she is sensitive and independent. Next, through reactions of other characters, she is smart, aggressive and ambitious. Those findings prove that as a female character, Maud also adopted masculinity traits. Kajian ini bertujuan untuk mengungkapkan bagaimana karakter perempuan digambarkan dalam film dan untuk membuktikan bahwa karakter perempuan juga mengadopsi sifat maskulinitas. Teori karakterisasi dari Boggs dan Petrie digunakan untuk mengungkap penggambaran karakter Maud, sementara untuk membuktikan bahwa Maud Watts mengadopsi sifat maskulinitas, penulis menggunakan teori Bem Sex Role Inventory dari Sandra L. Bem. Kajian ini dilakukan sebagai analisis isi kualitatif, yang mengadopsi teknik pengkodean kategori. Temuan kajian ini mengungkapkan bahwa sebagai karakter wanita, Maud tidak hanya mengadopsi sifat feminitas tetapi juga sifat maskulinitas. Karakter Maud digambarkan melalui lima alat karakterisasi menurut teori dari Boggs dan Petrie. Melalui penampilannya, Maud diketahui memiliki sifat maskulin dan menyenangkan. Melalui dialog, Maud mandiri, percaya diri, ambisius, tegas, kompetitif, simpatik, dan loyal. Melalui tindakan luarnya, Maud ambisius, simpatik, agresif, dan loyal. Melalui tindakan internalnya, dia sensitif dan mandiri. Selanjutnya, melalui reaksi dari karakter lain, Maud diketahui sebagai orang yang pintar, agresif dan ambisius. Temuan itu membuktikan bahwa sebagai karakter wanita, Maud juga mengadopsi sifat-sifat maskulinitas.